The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2000
DOI: 10.1016/s0014-5793(00)01814-7
|View full text |Cite
|
Sign up to set email alerts
|

A 45 kDa protein related to PPARγ2, induced by peroxisome proliferators, is located in the mitochondrial matrix

Abstract: Besides their involvement in the control of nuclear gene expression by activating several peroxisome proliferatoractivated receptors (PPARs), peroxisome proliferators influence mitochondrial activity. By analogy with the previous characterization of a mitochondrial T3 receptor (p43), we searched for the presence of a peroxisome proliferator target in the organelle. Using several antisera raised against different domains of PPARs, we demonstrated by Western blotting, immunoprecipitation and electron microscopy … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
41
0

Year Published

2002
2002
2016
2016

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 58 publications
(44 citation statements)
references
References 18 publications
3
41
0
Order By: Relevance
“…Peroxisome proliferators exert marked thyromimetic effects and are potent hypolipidaemic agents . In rats, peroxisome proliferators mediate the expression of genes regulated by thyroid hormone, including malic enzyme, mitochondrial glycerol-3-phosphate dehydrogenase, glucose-6-phosphate dehydrogenase and SPOT14 (Casas et al, 2000). The TSH deficiency of Pit1 dw/dwJ mice may also play a role in longevity determination owing to its function as a key regulator of various metabolic processes.…”
Section: Discussionmentioning
confidence: 99%
“…Peroxisome proliferators exert marked thyromimetic effects and are potent hypolipidaemic agents . In rats, peroxisome proliferators mediate the expression of genes regulated by thyroid hormone, including malic enzyme, mitochondrial glycerol-3-phosphate dehydrogenase, glucose-6-phosphate dehydrogenase and SPOT14 (Casas et al, 2000). The TSH deficiency of Pit1 dw/dwJ mice may also play a role in longevity determination owing to its function as a key regulator of various metabolic processes.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, the retinoic acid receptor RAR (62), the retinoid receptor alpha (RXRa) (60), the orphan receptor Nur 77/ TR3 (63,64), and the PPAR b-and c2-coactivator (PPARb-and c 2 ) related proteins (65) have been localized in mitochondria (Table 1). Among the nuclear transcription factors found in mitochondria are NF-jB, AP-1, CREB, p53, c-myc, wnt 13, Dok-4, HMG-A1, and c-src (reviewed in refs.…”
Section: The Presence Of Additional Nuclear Receptors and Other Nuclementioning
confidence: 99%
“…However, not all of the data support this theory and researchers have observed RARs outside of the nucleus (32). Receptors for thyroid (33), glucocorticoid (34-36), estradiol (37), and peroxisome proliferators (38) have been shown to localize to mitochondria. The two thyroid receptors found in the mt are truncated forms.…”
Section: Direct Regulation Of Mt Gene Expression By Steroid Hormones mentioning
confidence: 99%
“…This might suggest that additional factors are required for this DR2 to respond to thyroid hormone. Casas et al (38) reported that a truncated PPAR γ 2-like protein (mt-PPAR) bound this DR2 in a complex with TR/p43. This element has also been shown to act as a RARE in other genes (46 ).…”
Section: Direct Regulation Of Mt Gene Expression By Steroid Hormones mentioning
confidence: 99%